Leadership styles, organizational culture and organizational effectiveness: a study of multilatinas - Alvarez Echavarría, Ana Claudia (2018)
The relationship of leadership and organizational culture on performance has been empirically proven (Eppard, 2004), determining that the combination of transformational leadership and constructive culture yields in positive job performance, while on the contrary, transactional leadership and defensive culture has negative outcome. Given that both leadership and culture are constructs with differentiated variables (Bass & Avolio, 1993; Cooke & Szumal, 2000), different combinations of leadership style and organizational culture, could result in various outcome scenarios. Previous scholar findings about leadership and culture frameworks are abundant in developed economies, not so much in emerging regions such as Latin America, the latter with increasing importance in the worldwide economy. Particularly multilatinas, face the challenge of short term economic hurdles, outstanding therefore the importance of improving knowledge of leadership and organizational culture as key drivers for sustained growth and evolution. The objective for the proposed research was to identify the relationship between leadership style, organizational culture, and organizational effectiveness, in Latin American transnational corporations, or as so called, multilatinas. Surveys were implemented in three large multilatinas located in Central America and Andean region, in the retail, construction and food industries. Findings of the research pointed that the constructive culture was the most relevant variable in the development of higher attainment of organizational effectiveness, even beyond the transformational leadership. The Latin American multilatina leader was valued due to the heroic-ethic transformational profile in conjunction with the contingent reward transactional one. The ambiguity from followers appreciating a heroic leader, but at the same time demanding detailed direction from leaders, thus avoiding own responsibility, posed the need for future research for collective-empowering leadership rather than an individual one